2014
DOI: 10.1186/2193-1801-3-297
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma formosanum polysaccharides attenuate Th2 inflammation and airway hyperresponsiveness in a murine model of allergic asthma

Abstract: Allergic asthma is an inflammatory disease of the airways mediated by Th2 immune responses and characterized by airway hyperresponsiveness (AHR). Fungi of the genus Ganoderma are basidiomycetes that have been used in traditional Asian medicine for centuries. We recently found that PS-F2, a polysaccharide fraction purified from the submerged culture broth of Ganoderma formosanum, stimulates the activation of dendritic cells and primes a T helper 1 (Th1)-polarized adaptive immune response. This study was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Polysaccharide has many biological activities, such as antioxidant, antibacterial, antitumor, neuroprotection, immunomodulation, anti-inflammation, anticoagulant, improvement of hepatic function, and promotion of burn wound healing (Khoo, Abas, Abdullah, Mohd Tohit, & Hamid, 2014;Li & Shah, 2014;Pang et al, 2013;Pi, Wang, Lu, Lu, & Chen, 2014;Wang et al, 2014aWang et al, , 2014bXiao et al, 2014;Yang, Lu, Hsieh, & Lin, 2014a;Yang et al, 2014b). Jia, Yang, Wang, Liu, and Xie (2014) reported that polysaccharide from Laminaria japonica exhibited hypoglycemic and hypolipidemic activities in mice with experimentally induced diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Polysaccharide has many biological activities, such as antioxidant, antibacterial, antitumor, neuroprotection, immunomodulation, anti-inflammation, anticoagulant, improvement of hepatic function, and promotion of burn wound healing (Khoo, Abas, Abdullah, Mohd Tohit, & Hamid, 2014;Li & Shah, 2014;Pang et al, 2013;Pi, Wang, Lu, Lu, & Chen, 2014;Wang et al, 2014aWang et al, , 2014bXiao et al, 2014;Yang, Lu, Hsieh, & Lin, 2014a;Yang et al, 2014b). Jia, Yang, Wang, Liu, and Xie (2014) reported that polysaccharide from Laminaria japonica exhibited hypoglycemic and hypolipidemic activities in mice with experimentally induced diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…GF-P2 was later shown to stimulate macrophages via pattern-recognition receptors, Dectin-1, CR3, and TLR4, and to stimulate TNF-α production via the ERK and NK-κB pathways [ 6 ]. GF-P2 has also been shown to stimulate DC function and trigger Th1-polarized effects in ovalbumin-treated mice splenocytes, suggesting that PS-F2 can also activate an adaptive immune response against viruses and tumors [ 7 ]. Despite differences, PS-F2 and GF-EPS monosaccharide compositions are similar.…”
Section: Discussionmentioning
confidence: 99%
“…PS-F2 has also been shown to activate Dectin-1, CR3, and TLR4, as well as downstream Syk, JNK, p38, ERK, and NK-κB, which may in turn trigger innate immunity [ 6 ]. Using an airway hyperresponsiveness mice model, one study showed that PS-F2 inhibited airway hyperresponsiveness via reducing Th2 cytokines, interleukin (IL)-4, IL-5, and IL-13 [ 7 ]. Overall, the findings of previous research suggests that GF-EPS exhibits immunomodulatory effects on both innate and adaptive immunity in preclinical studies and may be potential material for application in cancer treatment, prevention, and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…PS-F2 functions as an adjuvant capable of inducing a Th1-polarized adaptive immune response, which would be useful in vaccines against viruses and tumors (Pi et al 2014b). The polysaccharide fraction purified from a culture broth of G. formosanum has been shown to have notable anticancer activity.…”
Section: Ganoderma Calidophilum G Carnosum G Chalceum and G Concmentioning
confidence: 99%